2018
DOI: 10.1038/s41589-018-0031-6
|View full text |Cite
|
Sign up to set email alerts
|

FINO2 initiates ferroptosis through GPX4 inactivation and iron oxidation

Abstract: Ferroptosis is a non-apoptotic form of regulated cell death caused by the failure of the glutathione-dependent lipid-peroxide-scavenging network. FINO2 is an endoperoxide-containing 1,2-dioxolane that can initiate ferroptosis selectively in engineered cancer cells. We investigated the mechanism and structural features necessary for ferroptosis initiation by FINO2. We found that FINO2 requires both an endoperoxide moiety and a nearby hydroxyl head group to initiate ferroptosis. In contrast to previously describ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
367
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 562 publications
(375 citation statements)
references
References 54 publications
(76 reference statements)
8
367
0
Order By: Relevance
“…Due to the iron‐dependent feature of FINO2 and the increased iron level in malignant cells, FINO2 is more potent in malignant cells compared with nonmalignant cells of the same tissue. Studies on the two enantiomers of FINO2 have shown that (−)‐FINO2 is more active and selective toward cancerous fibroblasts than (+)‐FINO2 . Moreover, in vitro experiments showed that chemoresistance‐related pathways (e.g., p53 mutation, BCL‐2 overexpression) can be bypassed by FINO2 (Figure H) …”
Section: Ferroptosis Inducers For Cancer Therapymentioning
confidence: 99%
“…Due to the iron‐dependent feature of FINO2 and the increased iron level in malignant cells, FINO2 is more potent in malignant cells compared with nonmalignant cells of the same tissue. Studies on the two enantiomers of FINO2 have shown that (−)‐FINO2 is more active and selective toward cancerous fibroblasts than (+)‐FINO2 . Moreover, in vitro experiments showed that chemoresistance‐related pathways (e.g., p53 mutation, BCL‐2 overexpression) can be bypassed by FINO2 (Figure H) …”
Section: Ferroptosis Inducers For Cancer Therapymentioning
confidence: 99%
“…By contrast, 1 S ,3 R ‐RSL3 (hereafter RSL3), and related molecules, covalently inactivate GPX4 by binding to the active site selenocysteine . GPX4 protein expression and/or activity can also be inhibited indirectly by the small molecules FIN56 and FINO 2 , through mechanisms that remain only partially characterized …”
Section: Introductionmentioning
confidence: 99%
“…The central ferroptotic regulator is glutathione peroxidase 4 (GPX4), which is the only known peroxidase capable of efficiently reducing esterified, oxidized fatty acids into unreactive alcohols 7 . Small molecules that trigger ferroptosis identified thus far include agents that inhibit GPX4 directly, molecules that deplete the GPX4 cofactor glutathione, and compounds that oxidize iron, all of which lead to lipid hydroperoxide accumulation 1,8 . Elevated lipid hydroperoxides lead to disruption of membrane architecture, production of reactive aldehydes, and ultimately cell death 9 .…”
mentioning
confidence: 99%